Collagen-Chitosan Hydrogel Formed in Situ Via Enzymatic Crosslinking - Sin Mun, Lau; Mohd Nadzir, Masrina; Roy Chowdhury, Shiplu; Fauzi Mh Busra, Mohd (International Journal of Engineering and Technology, 2018)
In this research, injectable collagen-chitosan conjugates (Col-Chit-Ph) hydrogel was formed by oxidative coupling of phenolic hydroxyl (Ph) groups in polymer chain via peroxidase-catalysed crosslinking reaction. The resulting Col-Chit-Ph solutions formed rapid hydrogel at physiological conditions by utilizing H2O2. The amount of chitosan in the compositions of Col-Chit-Ph hydrogels influenced the mechanical properties of the hydrogels. Here, conjugates having Col:Chit ratio of 1:1 showed greater resistance to compression compared to conjugates having Col:Chit ratio of 3:2. Meanwhile, the efficiency of cell attachment for conjugates with Col:Chit ratio of 4:1 is higher than conjugates with Col:Chit ratio of 1:1. Although the biological properties of hydrogel was good at Col:Chit ratio of 4:1, this hydrogel easily destroyed by external force. However, with higher amount of chitosan in the composite, hydrogels were more mechanically stable. This indicates the importance of the chitosan ratio to the novel Col-Chit-Ph injectable hydrogel composite.Â Â Â